Prominence of Information Richness in Accepting Online Based Self-Service Technologies - Badra Sandamali Galdolage (Archives of Current Research International, 2021)
Most of the service organizations are now moving to provide their services at a remote basis with Self-Service Technologies (SSTs). This is a natural outcome of technological maturity and would be the norm of many service transactions in future. Currently in many of the services, customers have the choice to use either SSTs or physical service encounters with service employees according to their desire. However, the future is predicted to replace many service employees with self-service machines and humanoid robots. Therefore, it is the responsibility of the service organizations to make their customers ready for such a future. Use of self-service technologies typically take place without the presence of organization’s service staff. Thus, machines should provide necessary guidance and instructions to customers so that they can perform well without difficulties. If SSTs are not rich with information, customers would be in trouble without proceeding with their transactions successfully. Therefore, the quality of information would be a matter for successful online based self -service transactions. Thus, the aim of this study is to understand the information richness in online based self-service technologies from the customer perspective. Using the qualitative approach, semi structured interviews were conducted with 25 individuals who have experience in using online based SSTs. The study found seven key factors which determine the richness of information in online platforms namely ‘Relevance, Timeliness, Accuracy, Clarity, Consistency, Sufficiency and Simplicity’. The study enriches the theoretical landscapes by broadening the understanding on significance of information richness in accepting online based self-service technologies while on practical ground provides insights for service providers in designing their SSTs with rich and necessary information which is required to perform successful transactions.